Identifying Markers of Differentiation in Monocyte-Derived-Macrophages - Gibson, Matthew Leo (University of the Witwatersrand, Johannesburg, 2024)
The importance of monocytes and monocyte-derived macrophages (MDMs) in both adaptive and innate immunity makes their study a topic of interest. Monocytes differentiate into macrophages through transcriptomic alterations, resulting in extensive changes in gene expression. Macrophage colony stimulating factor (M-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF) are the two primary cytokines that stimulate this differentiation, and are known to cause partial polarisation towards the M2 and M1 macrophage subtypes, respectively. However, the degree to which this polarisation takes place is not well-characterised. Therefore, this study aimed to use a computational approach to identify the differences and similarities in gene expression changes in macrophages induced with M-CSF and GM-CSF. RNA sequencing data for three human donors was obtained through EBI and used to quantify gene expression changes associated with M-CSF or GM-CSF treatment. Differential gene expression analysis was performed to identify the genes that were differentially expressed as a result of either treatment relative to the untreated monocytes. Over-representation analysis was used to determine the biological processes in which the differentially expressed genes (DEGs) were involved. Finally, transcription factors were identified within the lists of DEGs, as well as the genes encoding their known protein-protein interacting partners. Treatment with M-CSF and GM-CSF induced 4 072 and 4 399 DEGs, respectively, 2 734 of which were common. An examination of these DEGs revealed that the resultant macrophages lacked changes in expression of genes commonly associated with the M1 and M2 polarisation states. An investigation of the DEGs involved in myeloid cell differentiation and the regulation of inflammatory response revealed CCR2, IGF1 and INHBA to be inversely regulated by the two treatments. Furthermore, nine uniquely differentially expressed transcription factors involved in these biological processes were identified, each of which may be contributing to the lack of complete polarisation following differentiation. These results revealed that M-CSF and GM-CSF-induced macrophages, in the absence of activation, experience highly similar gene expression changes and lack changes in the expression of key polarisation marker genes.
Dissertation submitted in fulfilment of the requirements for the degree Master of Science, to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Bioinformatics; Differential Gene Expression; Immunology; Monocytes; Macrophages; RNA-seq; RNA sequencing; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education